Design a model strategy for regulations on the use of tobacco biopesticide as a substitute for hazardous pesticides - Irma Idris; Eka Setiawan; Maskun (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
Food security constitutes a pillar of national stability according to Law No. 18/2012, yet agricultural productivity is frequently threatened by pests. Chemical pesticides classified as Hazardous and Toxic Materials (B3) are effective but pose risks to health and the environment, induce pest resistance, and impose management burdens as stipulated in Government Regulation No. 22/2021. Tobacco possesses potential for utilization as a biopesticide due to the insecticidal properties of nicotine and its non-B3 classification. Through an empirical research approach integrating legal, agricultural, and environmental analyses, this study employed observation, interviews, regulatory analysis, literature review, and field effectiveness trials. The findings demonstrate that chemical pesticides require stringent management, which is frequently neglected; tobacco biopesticide is recognized under Minister of Agriculture Regulation No. 43/2019 and exhibits regulatory advantages; field trials reduced pest populations by up to 60% within four weeks after planting; implementation remains constrained by technological and research limitations. The utilization of tobacco biopesticide has the potential to reduce costs, mitigate B3 hazards, and support sustainable food security while empowering local farmers through principles of economic circularity, technological self-reliance, income diversification, ecosystem protection, and community empowerment aligned with food sovereignty.